Current perspectives of anoxic ammonia removal and blending of partial nitrifying and denitrifying bacteria for ammonia reduction in wastewater treatment. (June 2021) - Manasa, R L; Mehta, Alka
Graphical abstract: Highlights: Ammonia pollution in water bodies and the need for its removal. Anoxic and semi-anoxic bacterial enrichment in ammoniacal wastewater. The variance in the habitat, abundance and mechanism of the complete and partial ammonia reducing bacteria. Enzymes involved in the ammonia reducing processes. Coupling of complete and partial nitrifying bacteria involved in ammonia reduction. Abstract: Various anthropogenic activities and extensive urbanization are responsible for the generation of large amounts of wastewater containing toxic pollutants. Ammonia is one of the major pollutants in wastewater produced from households, industry and agriculture fields. Removal of ammonia during wastewater treatment is still a challenge. The conventional methods include two-step processes such as nitrification and denitrification. However, newly discovered processes of anammox and comammox seem to be more promising. This review elucidates on sources of ammonia contamination and its effects. Newly discovered process like anammox and comammox is discussed in detail. The habitat, abundance, the structure of bacteria and the chemical reactions involved in the processes are included in this review. Authors have brought out the analogy of the anammox process with the conventional nitrogen cycle and by coupling anammox with comammox to develop an efficient ammonia removal process.